SemLytics: Semantic Enrichment for FAIR Analytics Architectures - Araujo, Thiago Zero; Sedenho, Cecília Nunes; Castro, João Pedro de Carvalho; Santos, Bruno Jesus dos; Aguiar, Cristina Dutra (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2026.249647, 2026)
A key component of FAIR Analytics Architectures is the Semantic Enrichment Layer, which provides advantages such as enhancing interpretability and exploring complex relationships. However, developing this layer while addressing architectural specification, FAIR compliance, and semantic representation quality remains an unexplored challenge. In this paper, we propose SemLytics, a Semantic Enrichment Layer designed to address these issues. We present its logical level and demonstrate its implementation in a state-of-the-art FAIR analytics architecture. The results show that SemLytics improves FAIR compliance and semantic representation quality.